Arduino-Based Lab for Monitoring Biological Processes - ugli, Kuchkorov Akhlidin Mirzokhid; Xoshimovich, Karimov Bakhodir (International Journal on Orange Technologies, 2023)
This article discusses the design considerations and potential applications of an Arduino-based laboratory for monitoring biological processes. Biological processes such as microbial growth, plant growth, bioreactor operation, and fermentation require the monitoring of environmental factors like temperature, pH, and oxygen levels. The Arduino-based laboratory provides a low-cost, customizable, and user-friendly solution for monitoring these parameters. The article covers the selection of appropriate sensors, calibration methods, power supply considerations, data acquisition and storage techniques, environmental factors, user interface design, and safety measures for the laboratory. The transfer methods and Arduino code for data transfer using Bluetooth and SD card are also provided. The results obtained from monitoring nutrient availability, temperature, pH, and oxygen levels during microorganism propagation are presented, demonstrating the laboratory's accuracy and reliability. The discussion highlights the benefits of using the Arduino-based laboratory, including its low cost, open-source nature, user-friendliness, customization options, real-time monitoring capabilities, and potential for hands-on learning. The conclusion emphasizes the laboratory's accessibility, affordability, and potential to revolutionize the field of biotechnology by promoting collaboration, innovation, and high-quality research. Overall, the Arduino-based laboratory offers a promising solution for monitoring biological processes, providing valuable insights into the behavior of microorganisms and facilitating research and education in various settings.